Estimated number of people infected with hepatitis B and C virus in Germany in 2013: a baseline prevalence estimate using the workbook method - Katrin Kremer-Flach; Katrin Kremer-Flach; Katrin Kremer-Flach; Ruth Zimmermann; Matthias an der Heiden; Sandra Dudareva; Sandra Dudareva (Frontiers in Public Health)
IntroductionHepatitis B (HBV) and hepatitis C (HCV) viral infections are uncommon in Germany, though these infections have a higher prevalence among certain subpopulations, such as some first-generation migrant groups, people who inject drugs (PWID), and HIV-positive men who have sex with men (HIV+MSM). Repeated estimates of the number of people infected with HBV and HCV are essential to facilitate the monitoring and elimination efforts by 2030. We estimated the total number of people infected with HBV and HCV in Germany, and the number in each specific subpopulation. We based our calculations on data from 2013, a year that we strategically chose to coincide with the availability of data from serological surveys, the advent of highly effective antiviral therapy for HCV, and significant migrant flows in the following years.MethodsWe used the workbook method, a technique that combines subpopulation size and prevalence data. We included different population groups (general population excluding vulnerable groups, migrants stratified by nationality, people who inject opioids (PWIO) and HIV+MSM). We estimated the number of people infected with HBV and the number of people infected with HCV. Estimates of the number of people infected with HBV and HCV are reported with the lower and upper confidence limits.ResultsWe estimated 228,000 (179,000-291,000) HBV-infected adults (≥ 18 years of age) in Germany in 2013, of whom 41% (n = 93,000 [52,000–169,000]) were in the general population excluding vulnerable groups. Another 58% (132,000; 126,000-137,000) were migrants, 1.0% (2,400; 900–6,200) PWIO and 0.4% (1,000; 800–1,400) were HIV+MSM. We estimated 214,000 (135,000–340,000) HCV-infected adults in Germany in 2013, of whom 47% (100,000; 38,000–267,000) were in the general population excluding vulnerable groups, 26.0% (56,000; 47,000–66,000) were migrants, 26% (56,000; 50,000–62,000) were PWIO, and 1.0% (2,500; 2,200–2,800) were HIV+MSM, respectively.DiscussionOur results indicate that more than half of HBV-infected individuals were migrants, and more than half of HCV-infected individuals were PWIO or migrants. This highlights the importance of including relevant subpopulations in national estimates, surveillance, prevention, and therapy. Our estimates serve as a baseline reference for subsequent updates and ongoing monitoring of HBV and HCV epidemiology in Germany.